PENGARUH LAYANAN BIMBINGAN KONSELING TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS 3 SD NEGERI PASIR GOMBONG 06 KABUPATEN BEKASI - Ira Restu Kurnia; Nurmalia; Sri Rahayu; Nadhia Fatmawati; Aliya Rahmawati; Farahdila; Kristina Handayani; Siti Komariyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education in Indonesia is strongly influenced by the times and the development of the times will have a major influence on child development, problems that occur in the world of education are nothing more than the problem of child delinquency in schools, this shows the importance of the role of counseling guidance services for students when they are in situations that they think do not make them comfortable and this will have an impact on learning carried out in the classroom Because of the lack of learning motivation that learners have because of the discomfort itself. The purpose of this study is to find out the problems that often occur in schools that make students uncomfortable during the learning process so that their learning motivation decreases and try to find solutions to these problems so that students can feel comfortable, safe and happy in learning so that their learning motivation will increase and this will affect the learning outcomes of students. The research method used is a qualitative description approach by conducting direct observations and interviews at SDN Pasir Gombong 06 to identify whether there are problems that occur in the learning process that result in lack of student motivation and using data analysis related to various sources so as to strengthen the assumptions in the research we conducted. The results of this study are: 1) students feel comfortable and safe when there are adults watching them 2) students are more open in telling their problems when we ask questions well and slowly 3) students better understand how to act in class both towards educators and classmates 4) student learning motivation increases when they are happy and happy 5) students explore themselves in their own way, namely Such as: making noise because you want to be noticed or always asking questions because you want to be listened to.